Molecular Identification of Six New Benthic Fauna Records in the Andharmanik River, Bangladesh (Bioresearch Communications, 2025)
DNA barcoding has proven to be an effective alternative to traditional morphological methods for species identification. In this study, we employed a molecular approach to identify benthic fauna collected from the Andharmanik River estuary in Bangladesh. Mitochondrial cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA) genes were used as genetic markers for species delineation. A total of six benthic species—Cerebratulus lacteus, Maculaura magna, Maculaura cerebrosa, Perinereis cultrifera, Paralacydonia weberi, and Phyllodoce medipapillata—were reported for the first time in Bangladesh in this study. The mean interspecific genetic divergence, calculated using the Kimura 2-Parameter (K2P) model, was 39.72 ± 0.07% for 16S rRNA and 29.72 ± 0.03% for COI, indicating sufficient resolution for accurate species discrimination. Phylogenetic relationships were inferred using the Maximum Likelihood method, and individuals belonging to the same species consistently formed species-specific clades. This study presents the first DNA barcoding-based identification of polychaete and nemertean species in Bangladesh.Bioresearch Commu. 11(2): 1874-1880, 2025 (July)